1996 amines plant explosion. Issue 2 (6th August 2015) - Forest, Jerry
Abstract : Process safety management systems should be in place to ensure repeatability in operations. A good system consists of higher level procedures that describe what to do. At the plant level, the management system describes who does the activity and how it is done. Following procedures leads to predictability in operations. In 1996, Celanese had established a rigorous management system that consisted of 21 elements of process safety. However, before the elements could be fully implanted globally, failure to rigorously apply several elements led to an explosion in our Cangrejera facility resulting in two fatalities. This article discusses the management system failures of conduct of operations elements, safe operating limits, standard operating procedures and training, and critical safety equipment management and how each failed due to a common weakness of management systems. An overview of the Celanese Process Safety Lessons Learned program is presented as our way of embedding knowledge of this and other incidents in our culture to prevent similar incidents in the future. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 149–152, 2016